Expedient Approach to the Synthesis of Betrixaban - Raji Reddy, Chada; Sinare, Sudam N. (SynOpen, 2020)
A new scalable route to synthesize the factor Xa (FXa) inhibitor betrixaban is disclosed. The product is obtained in a seven-step reaction sequence (in five stages using two one-pot reactions) starting from easily accessible 4-(N,N-dimethylcarbamimidoyl)benzoate. Effective isolation of intermediates, use of cost-effective amide formation and 2-methyltetrahydrofuran as an effective reaction solvent as well as for extraction in three of the stages, are key features. The strategy provides the desired product in 38% overall yield with high purity (>98%).
Keywords: betrixaban; factor Xa (FXa) inhibitor; anticoagulant; one-pot reaction; amidation